IFN-γ orchestrates tumor elimination, tumor dormancy, tumor escape, and progression. Issue 6 (22nd February 2018) - Aqbi, Hussein F; Wallace, Matthew; Sappal, Samay; Payne, Kyle K; Manjili, Masoud H
Abstract: Tumor immunoediting consisting of three phases of elimination, equilibrium or dormancy, and escape has been supported by preclinical and clinical data. A comprehensive understanding of the molecular mechanisms by which antitumor immune responses regulate these three phases are important for developing highly tailored immunotherapeutics that can control cancer. To this end, IFN-γ produced by Th1 cells, cytotoxic T cells, NK cells, and NKT cells is a pleiotropic cytokine that is involved in all three phases of tumor immunoediting, as well as during inflammation-mediated tumorigenesis processes. This essay presents a review of literature and suggests that overcoming tumor escape is feasible by driving tumor cells into a state of quiescent but not indolent dormancy in order for IFN-γ-producing tumor-specific T cells to prevent tumor relapse. Abstract : Review on the mechanisms by which IFN-gamma manifests paradoxical functions of relevance to developing highly tailored immunotherapeutics for cancer patients.